Pertanggungjawaban Hukum Direksi PT. Bank Jawa Barat & Banten Atas Pembelian Gedung Kantor Pada Putusan Mahkamah Agung RI No. 2301K/PID.SUS/2016 Jo. Putusan Tipikor Pada Pengadilan Negeri Bandung No. 147/Pid.Sus-TPK/2015/PN.Bdg - Robinson Sihombing; Alvi Syahrin; Muhammad Hamdan; Mahmul Siregar (Universitas Sumatera Utara, 2019)
Abstract : The Anti-Corruption Law has been enacted for a long time but still corruption cannot be eradicated and even tends to increase from year to year, both in quality and quantity. Corruption is an act that is very detrimental to the country's finances and afflicting society at the same time can hamper national development. Therefore, corruption is classified as an extraordinary dispute that needs to be eradicated completely, as if by increasing the workforce and the forced power of existing laws and regulations, both through law enforcement, also through civil law enforcement. Corruption is any activity to enrich oneself or another person or one who can help finance or the country. This study reinforces the idea that the procurement of goods and services is an easy target for corruptors. The court's decision related to the corruption case mentioned above, namely: Decision of the Supreme Court No. 2301K/PID.SUS/2016, dated July 26, 2017 Jo. Decision of Corruption in Bandung District Court No. 147/Pid.Sus-TPK/2015/PN.Bdg., Dated December 14, 2015 which has permanent legal force (inkracht). Interestingly the case in this ruling was discussed because, in the first instance decision Defendant Wawan Indrawan was acquitted of all charges of the Public Prosecutor (vrijspraak). After the Public Prosecutor filed an appeal to the Supreme Court, the panel of judges overturned the verdict of the first instance and subsequently declared the Defendant guilty of committing corruption together with imprisonment for 8 (eight) years and a fine of Rp. 1.000.000.000,- (one billion rupiah) subsidair 8 (eight) months of confinement. Keywords : Procurement; directors; and Bank